Heme–Hemopexin Complex Attenuates Neuronal Cell Death and Stroke Damage. Issue 4 (April 2014) - Li, Rung-chi; Saleem, Sofiyan; Zhen, Gehua; Cao, Wangsen; Zhuang, Hean; Lee, Jongseok; Smith, Ann; Altruda, Fiorella; Tolosano, Emanuela; Doré, Sylvain
Correction to : Journal of Cerebral Blood Flow & Metabolism (2009)29, 953–964; doi:10.1038/jcbfm.2009.19 After the publication of this article, errors in the Materials and Methods section were noticed. The section on immunofluorescence should read: IMMUNOCYTOFLUORESCENCE STAINING AND FLUORESCENCE MICROSCOPY: Cultured embryonic neurons were grown on poly-D -lysine-coated glass coverslips for 10 days. The neurons then were permeabilized for 2 mins with 0.5% Triton X-100 followed by fixation with 3% paraformaldehyde for 20 mins at room temperature. The cells were incubated with primary antibodies to microtubule-associated protein (MAP2, a neuronal marker; Chemicon International) and to HPX for 30 mins, washed, and then incubated with rhodamine-conjugated, affinity-purified donkey anti-goat IgG (H+L) and FITC-conjugated, affinity-purified goat anti-rabbit IgG (H+L) (Jackson ImmunoResearch Laboratories, West Grove, PA, USA) secondary antibodies for 30 mins. For fluorescence microscopy, cells were observed by epifluorescence on a Nikon TE-200 microscope. Images were captured with a CoolSNAP HQ camera (Image Processing Solutions Inc., North Reading, MA, USA) with OpenLab software (Improvision Inc., Boston, MA, USA).